PENGARUH INFLASI DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM - Muhlis, Muhammad; Nugroho, Hendrato Setiabudi (Program Studi Manajemen, 2022)
The capital market in Indonesia has experienced quite good growth. This is indicated by the increase in average stock trading on the Indonesia Stock Exchange, where one of the sub-sectors that have high purchasing power is pharmaceutical companies. This condition is inseparable from the current economic situation in Indonesia. One of the government's efforts in dealing with economic problems is to suppress the inflation rate and increase the rupiah exchange rate. This study aims to determine the effect of inflation and exchange rates on the stock price index of pharmaceutical sub-sector companies. The methods and analysis used were classical assumption test, multiple linear regression analysis, and hypothesis testing which consisted of t test, f test, and coefficient of determination. The results obtained after data analysis showed that partially the inflation had no effect on the stock price index, while the exchange rate had an effect on the stock price index. Simultaneously the inflation and exchange rate affected the stock price index.